A systematic review of the association between dementia risk factors and cerebrovascular reactivity - Wang, C; Reid, G; Mackay, CE; Hayes, G; Bulte, DP; Suri, S (Elsevier, 2023)
Cumulative evidence suggests that impaired cerebrovascular reactivity (CVR), a regulatory response critical for maintaining neuronal health, is amongst the earliest pathological changes in dementia. However, we know little about how CVR is affected by dementia risk, prior to disease onset. Understanding this relationship would improve our knowledge of disease pathways and help inform preventative interventions. This systematic review investigates 59 studies examining how CVR (measured by magnetic resonance imaging) is affected by modifiable, non-modifiable, and clinical risk factors for dementia. We report that non-modifiable risk (older age and apolipoprotein ε4), some modifiable factors (diabetes, traumatic brain injury, hypertension) and some clinical factors (stroke, carotid artery occlusion, stenosis) were consistently associated with reduced CVR. We also note a lack of conclusive evidence on how other behavioural factors such as physical inactivity, obesity, or depression, affect CVR. This review explores the biological mechanisms underpinning these brain-behaviour associations, highlights evident gaps in the literature, and identifies the risk factors that could be managed to preserve CVR in an effort to prevent dementia.